Red lesions: vascular lesions - Sciubba, James J. (Henry Stewart Talks, 2017)
Vascular proliferations, Hemangioma, Vascular malformations, Varicosities/Venous lakes, Hereditary hemorrhagic telangiectasia, Peripheral giant cell granuloma, Pyogenic granuloma, Kaposi sarcoma, Hypersensitivity lesions, Plasmacytic gingivitis, Erythema multiforme, Microbial/Infectious lesions, Candidiasis, Median rhomboid glossitis, Syphilis